Survival, but not the severity of hypoxic–ischemic encephalopathy, is associated with higher mean arterial blood pressure after cardiac arrest: a retrospective cohort study - Preuß, Sandra; Multmeier, Jan; Stenzel, Werner; Major, Sebastian; Ploner, Christoph J.; Storm, Christian; Nee, Jens; Leithner, Christoph; Endisch, Christian (Frontiers in Cardiovascular Medicine, 2024)
Background: To study the association between mean arterial blood pressure (MAP), vasopressor requirement, and severity of hypoxic-ischemic encephalopathy (HIE) after cardiac arrest (CA).Methods: Between 2008 and 2017, we retrospectively analyzed the MAP 200 hours after CA and quantified vasopressor requirements using the cumulative vasopressor index (CVI). Using postmortem brain autopsy in nonsurvivors, the severity of HIE was histopathologically dichotomized into no/mild and severe HIE. In survivors, we dichotomized the HIE severity into no/mild -Cerebral Performance Category (CPC) 1 -and severe HIE (CPC 4).Regain of consciousness, death causes and five-day survival were investigated as hemodynamic confounders.Results: Among 350 non-survivors, 117 had histopathologically severe HIE and 233 no/mild HIE without differences in MAP (73.1 vs 72.0 mmHg, pgroup=0.639). Compared to non-survivors, 211 CPC 1 and 57 CPC 4 patients had higher MAPs that showed significant, but clinically non-relevant MAP differences (81.2 vs 82.3 mmHg, pgroup<0.001). No/mild HIE non-survivors (n=54) regaining consciousness before death had higher MAPs compared to no/mild HIE non-survivors (n=179) who remained persistently comatose (74.7 vs 69.3 mmHg, pgroup<0.001). No/mild HIE non-survivors regaining consciousness required less vasopressors (CVI 2.1 vs 3.6, pgroup<0.001). Independently of HIE severity, survivors were faster weaned from vasopressors (CVI 1.0).Higher MAP was associated with survival but not HIE severity in CA patients treated with a vasopressor-supported MAP target above 65 mmHg. Awakening from coma was associated with less vasopressor requirements. Our results provide no evidence for a MAP target above current guideline recommendations to decrease the severity of HIE.